Origins of COVID-19: A Comprehensive Analysis of Zoonotic Drift Patterns and Gain-of-Function Research - Sanjay Pooran (Ukrainian Policymaker)
The COVID-19 pandemic has not only posed an unprecedented health crisis but has also escalated into a critical geo-political and political issue worldwide. This paper analyzes the origins of SARS-CoV-2, examining zoonotic drift patterns and the controversial role of gain-of-function (GoF) research. The zoonotic spillover hypothesis, emphasizing the virus’s natural emergence, and the lab-origin hypothesis, exploring its potential laboratory escape, are critically evaluated. Understanding the virus’s origins is crucial for strengthening global health policies, biosafety regulations, and pandemic preparedness. The pandemic’s global socio-political implications highlight the urgency for international cooperation and transparency to mitigate future health and security challenges.